UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BUAH KEMUKUS (Piper cubeba L.F) TERHADAP BAKTERI Escherichia coli DAN Staphylococcus aureus - siti zurai da (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id)
Experimental activity of antibacterial activity of ethanol extract of fruit of kemukus (Piper cubeba L.F) was done to find out the secondary metabolite and antibacterial activity of ethanol extract of fruit (Piper cubeba L.F) against Escherichia coli and Staphylococcus aureus bacteria. The method used was agar diffusion method at concentrations of 80, 40, 20, and 10%. The results showed that the ethanol extract of the steamed fruit had an inhibitory diameter area of ​​8.6; 8.1; 7.5 and 7.3 are antibacterial in the weak category against Escherichia coli, whereas against Staphylococcus aureus has a diameter of the inhibitory area of ​​8.9, respectively; 8.7; 7.6 and 7.5 are antibacterial in the weak category.